Berberine inhibits IFN-γ signaling pathway in DSS-induced ulcerative colitis - Tao Yang; Xiao Ma; Ruilin Wang; Honghong Liu; Shizhang Wei; Manyi Jing; Haotian Li; Yanling Zhao (Elsevier, 2022)
Aims: The potential signaling pathways and core genes in ulcerative colitis (UC) were investigated in this study. Furthermore, potential mechanisms of BBR in treating UC were also explored. Methods: Expression profiling by array of UC patients were obtained from Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were determined with the differential analysis. The biological functions of DEGs were analyzed through the Database for Annotation, Visualization and Integrated Discovery (DAVID). The Gene Set Enrichment Analysis (GSEA) was applied to analyze the expression differences between two different phenotype sample sets. Dextran sulfate sodium (DSS) was applied to establish UC model of mice and lipopolysaccharide (LPS) was utilized to induce inflammatory damage of NCM460 cells. Therapeutic effects of berberine (BBR) on disease performance, pathologic changes and serum supernatant indices were analyzed in vivo. To further investigate the potential mechanisms of BBR in treating UC, the expression of genes and proteins in vivo and in vitro were examined by RT-qPCR, immunohistochemical staining and western blotting. Results: Immune-inflammatory genes were identified and up-regulated significantly in UC patients. In addition, IFN-γ signaling pathway and its core genes were significantly up-regulated in the phenotype of UC. All disease performance and the pathologic changes of UC in mice were evidently ameliorated by BBR treatment. The pro-inflammatory cytokines of serum, including CXCL9, CXCL1, IL-17 and TNF-α, in UC mice were significantly reduced by treatment of BBR. In terms of mechanisms of BBR in treating UC, the pro-inflammatory and immune-related genes, encoding IFN-γ, IRF8, NF-κB and TNF-α decreased significantly in UC mice followed by BBR treatment. Meanwhile, the expression of IFN-γ and its initiated targets, including IRF8, Ifit1, Ifit3, IRF1, were suppressed significantly by BBR treatment in vivo. The blocking of IFN-γ in vitro led to the silence of IFN-γ signaling pathway after exposure to BBR. Furthermore, the blocking of IFN-γ in vitro led to the silence of IFN-γ signaling pathway after exposure to BBR. Conclusion: BBR holds anti-inflammatory activity and can treat UC effectively. The anti-inflammatory property of BBR is tightly related to the suppression of IFN-γ signaling pathway, which is crucial in immune-inflammatory responses of the colon mucosa.